Foreign Direct Investment and Economic Growth in Romania's Development Region North-East - Ovidiu Serafim Trufin (CES Working Papers, 2010)
One of integration's advantages it is represented by the increasing grade of economic opening toward the rest of the world, with benefic effects over intercepted foreign direct flows, reciprocal flows of working force and work productivity. Given this context and taking into account analyses presented in our research, I appreciate that North – East Developing Region will further attract larger flows of foreign direct investments, flows that will in turn accelerate, through chain effect, the process of regional development.
Keywords: 330; foreign direct investments; economic growth; development regions; regional dissimilitude; competitive advantages